RESONANT GEOCHEMICAL RESPONSE OF OIL-BEARING STRATUM TO A SEISMIC STIMULUS - Nikolayev A.V.; Voytov G.I.; Kuznetsov V.V.; Ammosov S.M.; Khavroshkin O.B.; Teytel'baum Y.M.; Katsonis A.N.; Saprykin L.V.; Kir'yanova G.S. (My University, 1989)
Empirical data indicate that many properties of ground water and gas systems are unstable, e.g., the water films sorbed on the rock matrix, the oil-gas ratio and viscosity of the liquid, intrapore turbulence, dilatancy volumes, surface tension of the oil-water interface, and so on. These systems show up in the elastic wave fields over a wide range of frequencies, from a few hertz to tens or even hundreds of kHz, so that even very weak seismic stimuli can produce strong effects. We investigated the effect of seismic vibrations on the accessory gases of a reservoir rock. We have identified a previously unknown phenomenon of molecular breakdown of accessory hydrocarbon gases and the generation of relatively unstable (unsaturated) petroleum hydrocarbons in a complex multiphase stratal fluid acted on by elastic waves, with the maximum efficiency of the process occurring at the preferred frequencies of 11 and 13 Hz. Resonance phenomena also occur in the response of groundwater to vibrations, but the resonant frequencies vary with the conditions. We therefore conclude that resonance in the response to vibrations is a rather general geochemical phenomenon that may play a major role in the generation and evolution of oil fields and could be helpful in the stimulated rejuvenation of oil-bearing formations by vibrational treatment.